CALCULATION OF THE SPATIAL DEPENDENCE OF TEMPERATURE AND TEMPERATURE INSTABILITY OF THERMOELEMENTS (Scientific journal of the Fergana State University, 2024)
The advantages of the thermoelectric cooling method (small dimensions and weight of thermoelements, absence of moving parts, relatively short ramp-up time, etc.) make it possible in some cases to give preference to thermoelectric cooling devices over compression and absorption type refrigeration devices.